Mechanical Properties Evaluation of Welded Joints of Stainless Steel 304L and Low Carbon Steel Using (TIG) Welding Techniques - Taher M. Alabani; Thoria G. Sharef; Esmail R. Elsughayiere; Omaema M. Alkabat (African Journal of Advanced Pure and Applied Sciences, 2023)
Stainless steels are widely used in, nuclear reactors, thermal power plants, vessels, automobiles components and heat exchangers for several industrial applications due to their superior fracture toughness, good inter granular corrosion resistance and non-requirement of post process annealing. The dissimilar metal joints of have been emerged as a structural material for various industrial applications which provides good combination of mechanical properties like strength, corrosion resistance with lower cost. Selections of joining process for such a material are difficult because of their physical and chemical properties. In this research study the effect of nickel alloy buffer layer (ERNiCrMo-3) on low carbon steel to evaluation mechanical properties of dissimilar metal joints welded of stainless steel 304L and low carbon Steel using (TIG) welding techniques. Specimens stainless steel of grades 304L was welded with specimen's low carbon steel by Tungsten Inert Gas (TIG) processes by Nickel alloy buffer layer first stage on low carbon steel and second stage without buffers layer. The process parameters like current, voltage, and weld speed, gas flow was putted. Tensile strengths of welded test samples with Nickel alloy buffer layer vary from 461 to 529MP depending upon the welding conditions. And is record the highest tensile strengths at 110A is 529MP and tensile strengths of welded test samples without buffer layer is record at 90A is 522MP. Depending upon the welding conditions. The results were compared for different joints welded it was observed that dissimilar metal joints by Nickel alloy buffer layer have better than without buffer layer and use special application. The microstructure was analysis and hardness were calculated and obtained good values.